PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Felicia; Kartina Natalylova (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to analyze the factors that influence management actions in non-financial companies listed on the Indonesia Stock Exchange. The factors that become independent variables in this research are leverage, profitability, liquidity, firm size, firm age, institutional ownership, and audit quality on earnings management. This study uses data from 477 companies that have met the sampling criteria from 2017 to 2020 using the purposive sampling method. The results of this study indicate that the profitability variable has a significant effect on earnings management, meaning that the current high level of profitability makes the opportunity for future profitability declines to be greater, so that the company's performance looks less stable. The audit quality variable also has a significant effect on earnings management because good audit quality will make it difficult for companies to carry out earnings management. While the other independent variables, leverage, liquidity, firm size, firm age, and institutional ownership have no significant effect on earnings management.